LamNI – an instrument for X‐ray scanning microscopy in laminography geometry. (6th April 2020) - Holler, Mirko; Odstrčil, Michal; Guizar-Sicairos, Manuel; Lebugle, Maxime; Frommherz, Ulrich; Lachat, Thierry; Bunk, Oliver; Raabe, Joerg; Aeppli, Gabriel
Abstract : A technical description of an instrument that allows 3D nano‐imaging via ptychographic X‐ray laminography is presented. Abstract : Across all branches of science, medicine and engineering, high‐resolution microscopy is required to understand functionality. Although optical methods have been developed to `defeat' the diffraction limit and produce 3D images, and electrons have proven ever more useful in creating pictures of small objects or thin sections, so far there is no substitute for X‐ray microscopy in providing multiscale 3D images of objects with a single instrument and minimal labeling and preparation. A powerful technique proven to continuously access length scales from 10 nm to 10 µm is ptychographic X‐ray computed tomography, which, on account of the orthogonality of the tomographic rotation axis to the illuminating beam, still has the limitation of necessitating pillar‐shaped samples of small ( ca 10 µm) diameter. Large‐area planar samples are common in science and engineering, and it is therefore highly desirable to create an X‐ray microscope that can examine such samples without the extraction of pillars. Computed laminography, where the axis of rotation is not perpendicular to the illumination direction, solves this problem. This entailed the development of a new instrument, LamNI, dedicated to high‐resolution 3D scanning X‐ray microscopy via hard X‐ray ptychographic laminography. Scanning precision is achieved by a dedicated interferometry scheme and the instrument covers a scan range of 12 mm × 12 mm with a position stability of 2 nm and positioning errors below 5 nm. A new feature of LamNI is a pair of counter‐rotating stages carrying the sample and interferometric mirrors, respectively.